2011
DOI: 10.1136/adc.2010.204552
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics of intravenous paracetamol in neonates: size matters most

Abstract: Patient size (predicted by weight) is the major covariate of clearance variance in neonates. Using these estimates, a mean paracetamol serum concentration of 11 mg/l is predicted in neonates of 32-44 weeks' PMA given a standard dose of intravenous paracetamol of 10 mg/kg every 6 h. Safety data for this drug are limited in neonates. Continued surveillance therefore remains essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
142
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 129 publications
(150 citation statements)
references
References 34 publications
(45 reference statements)
5
142
3
Order By: Relevance
“…Recent data from Allegaert et al showed that variance in clearance of intravenous paracetamol is primarily explained by weight and suggests that dosing of intravenous paracetamol should be based on weight instead of PMA [15].…”
Section: Discussionmentioning
confidence: 99%
“…Recent data from Allegaert et al showed that variance in clearance of intravenous paracetamol is primarily explained by weight and suggests that dosing of intravenous paracetamol should be based on weight instead of PMA [15].…”
Section: Discussionmentioning
confidence: 99%
“…Data on the clinical pharmacology of acetaminophen, including pharmacokinetics and tolerance (hepatic, hemodynamics) in neonates following either enteral or intravenous route, have been published. Clearance mainly relates to weight, age, and-to a limited extent-hyperbilirubinemia [174,175]. Hepatic tolerance and hemodynamic tolerance have been documented during repeated administration [173].…”
Section: Acetaminophen (Paracetamol)mentioning
confidence: 99%
“…In addition to oral and rectal formulations, several intravenous (IV) formulations became available more recently. Such a formulation enables the administration of acetaminophen when the enteral route cannot (yet) be used and should improve the predictability by the reduction in variability related to absorption [173][174][175]. Intermittent (p.r.n.)…”
Section: Acetaminophen (Paracetamol)mentioning
confidence: 99%
“…In stratified analysis, the cumulative morphine dose in the acetaminophen group compared with the morphine group was 49% lower among neonates aged 0 through 10 days (median dose, 111 g/kg per 48 hours vs 218 g/kg per 48 hours, respectively) and was 73% lower among infants aged 11 through 365 days (median dose, 152 g/kg per 48 hours vs 553 g/kg per 48 hours). For a study designed to investigate the efficacy of acetaminophen, it is arguable that collapsing the age-related strata should have been based on the pharmacokinetics of acetaminophen 7,8 rather than morphine. Nevertheless, reporting data on morphine dose reductions according to the age-group strata originally designed in this study will be of interest for clinicians.…”
mentioning
confidence: 98%
“…To allow clearer assessment of risk-benefit ratios, however, prospective studies evaluating the safety of intravenous acetaminophen are essential before any recommendations can be made regarding its routine clinical use in the postsurgical care of infants. Because acetaminophen clearance is decreased with lower gestational and postnatal age, 7,8 one major concern is that prescribing long-term, standard doses every 6 hoursparticularly for younger children or those with critical illness or poor enteral nutrition-may lead to toxicity. Future studies should not only monitor renal function and liver function but also should measure acetaminophen-protein adducts in all children, particularly neonates, receiving intravenous acetaminophen.…”
mentioning
confidence: 99%